Penerapan Play Therapy dengan Permainan Tradisional dalam Mengembangkan Interaksi Sosial Siswa di SMP N 8 Kota Jambi - Affan Yusra; Rasimin Rasimin (JPM: Jurnal Pengabdian Masyarakat, 2022)
This devotion is intended to see the role play of therapy in developing the students' interactions of the eight cities of jambi. The PKM implementation activity USES the classification setting by using the use of therapy in developing student social interaction through the following method:1) the social method: through this method a process of planting or transfer of habits in one generation to the next generation can be through individual, group and masayrakat forms. The method is used to provide several explanations of social interaction and therapeutic guide play, as well as opinions. 2) methods of play therapy: these methods are developed on a basis of mature concepts, in which they help train students in order to prevent and overcome obstacles, and help students achieve their reproductive assignments. Through this method students are trained to communicate by using good language in performing cooperation and training social contact between students.